After the spotlight: are evidence-based recommendations for refeeding post-contest energy restriction available for physique athletes? A scoping review. Issue 1 (31st December 2022) - Chica-Latorre, Sara; Buechel, Claire; Pumpa, Kate; Etxebarria, Naroa; Minehan, Michelle
ABSTRACT: Background: To date, there is limited consensus on post-contest recovery recommendations for natural physique athletes. The available literature emphasizes the negative consequences of extreme dieting associated with physique contests, yet offers only speculative suggestions to facilitate physiological recovery post-contest. This scoping review evaluates evidence-based recommendations for recovery in post-physique contests. Methods: The online search engines and databases Google Scholar, PubMed, and Scopus were searched systematically and 12 peer reviewed journal articles were included in the review. Results: Six key factors were identified that directly impacted on physiological recovery post-contest: (1) body composition, (2) recovery dietary intake, (3) resting metabolic rate (RMR) restoration, (4) endocrine measures recovery, (5) menstrual cycle recovery, and (6) psychological aspects of recovery. Conclusions: Three dietary strategies have been proposed to facilitate physiological recovery post-contest while bearing in mind body composition and future athlete outcomes; (1) a gradual increase in energy intake to maintenance requirements, (2) ad libitum eating, (3) an immediate return to maintenance energy requirements. Future research is required to determine the timeline in which full physiological recovery occurs post-contest and which strategies best support athlete health and performance during post-contest recovery.